INTEGRASI MODEL HOUSE OF RISK DAN ANALYTICAL NETWORKING PROCESS (ANP) UNTUK MITIGASI RISIKO SUPPLY CHAIN - Natalia, Christine; Oktavia, Chendrasari Wahyu; Makatita, Welhelmina Vince; Suprata, Ferdian (Metris: Jurnal Sains dan Teknologi, 2021)
Currently, the resilience of the company is not separated from the strength supply chain network. Without this network, so the business process will not run well. But the strong supply chain network became vulnerable to risk. It caused by complexity and a highly dependent supply chain network. These risks need to minimize. The method that can be used to minimize risk with integrating the house of risk method and Analytical Network Process. The purpose of these integration methods to identification and recognized interrelationships between risk agent’s mitigation strategies, so the effect of event risk can be reduced. And then, by looking strategies can reducing costs incurred by the company and efficiency of risk agent’s mitigation strategy. Based on the results of House of Risk stage 1, there are 25 causes of risk that need to mitigate. The risk mitigation strategies that obtained to minimize the causes of risk, are then processed by the Analytical Networking Process (ANP) method. Based on the results of the Analytical Networking Process (ANP) method, there are two risk mitigation strategies. House of Risk stage 2 has applied to measure the efficiency and the level of difficulty of these two risk mitigation strategies. The results showed that the best mitigation strategies are conducting training and measuring company’s performance.